Control Strategy for Stabilization of the Biped Trunk-SLIP Walking Model - Minh Nhat Vu; Oh, Yonghwan; Lee, Jongwoo (2017 14TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2017)
In this paper, we present a new control strategy for the Bipedal Trunk Spring Loaded Inverted Pendulum (BTSLIP) model, consisting of springy legs and rigid trunk. Our walking controller is inspired from the Virtual Pendulum (VP) concept. In this concept, by intersecting the ground reaction forces (GRF) to a virtual pivot point (VPP), the trunk is provided the restoring moment to keep its balance and to behave like a virtual hanging pendulum. The simple hip torque control was presented with the name the VPP method. However, this approach is not reliable in terms of rejecting disturbances. Thus, we propose a new control strategy to achieve the robustness and stabilize the walking gait. Herein, the control is introduced with the combination of two strategies, 1) updating the position of the VPP by using Discrete Linear Quadratic Regulator controller and 2) controlling the stiffness of springy legs by feedback linearization controller to track both reference vertical position and velocity of the Center of Mass (CoM). We present the dynamic simulation of the BTSLIP model under the presence of external disturbances. The performance of the proposed control strategy shows stable, robust walking which is compared with the VPP method.